Let r , s , and t be the three roots of the equation 8 x 3 + 1 0 0 1 x + 2 0 0 8 = 0 .
Find ( r + s ) 3 + ( s + t ) 3 + ( t + r ) 3
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice use of Newton's Identities!
Is it really worth LEVEL 5.What do you think bro...isn't it overrated
Simple use of Vieta’s give us r+s+t=0, r*s*t=-2008/8=-251, gives r+s=-t, s+t=-r, t+r=-s. ∴ G i v e n E x p . = − ( t 3 + r 3 + t 3 ) . B u t − ( t 3 + r 3 + t 3 ) + 3 ∗ r ∗ s ∗ t = − ( r + s + t ) ∗ f ( r , s , t ) = 0 ∗ f ( r , s , t ) = 0 . ∴ − ( t 3 + r 3 + t 3 ) + 3 ∗ r ∗ s ∗ t = 0 ⟹ E x p . = − ( t 3 + r 3 + t 3 ) = − 3 ∗ r ∗ s ∗ t = − 3 ( − 2 5 1 ) = 7 5 3
By Vieta's, r + s + t = 0 , so we can rewrite ( r + s ) 3 + ( s + t ) 3 + ( t + r ) 3
as ( 0 − t ) 3 + ( 0 − r ) 3 + ( 0 − s ) 3 = − t 3 − r 3 − s 3 = − ( t 3 + r 3 + s 3 )
Let P k = r k + s k + t k
By Newton's Sums, 8 P 3 + 3 ⋅ 2 0 0 8 = 0 ⟹ P 3 = − 8 3 ⋅ 2 0 0 8 = − 7 5 3
So the answer is − P 3 = 7 5 3
Problem Loading...
Note Loading...
Set Loading...
By Vieta's formulas , we have r + s + t = 0 , and so the desired answer is ( r + s ) 3 + ( s + t ) 3 + ( t + r ) 3 = ( 0 − t ) 3 + ( 0 − r ) 3 + ( 0 − s ) 3 = − ( r 3 + s 3 + t 3 ) . Additionally, using the factorization r 3 + s 3 + t 3 − 3 r s t = ( r + s + t ) ( r 2 + s 2 + t 2 − r s − s t − t r ) = 0 we have that r 3 + s 3 + t 3 = 3 r s t . By Vieta's again, r s t = 8 − 2 0 0 8 = − 2 5 1 ⟹ − ( r 3 + s 3 + t 3 ) = − 3 r s t = 7 5 3 .